Use of selective gut decontamination in critically ill children: protocol for the Paediatric Intensive Care and Infection Control (PICnIC) pilot study. Issue 3 (11th March 2022) - Brown, Alanna; Ferrando, Paloma; Popa, Mariana; de la Fuente, Gema Milla; Pappachan, John; Cuthbertson, Brian; Drikite, Laura; Feltbower, Richard; Gouliouris, Theodore; Sale, Isobel; Shulman, Robert; Tume, Lyvonne N; et al.
Abstract : Introduction: Healthcare-associated infections (HCAIs) are a major cause of morbidity and mortality in critically ill children. In critically ill adults, there are data that suggest the use of Selective Decontamination of the Digestive tract (SDD), alongside standard infection control measures reduce mortality and the incidence of HCAIs. SDD-enhanced infection control has not been compared directly with standard infection prevention strategies in the Paediatric Intensive Care Unit (PICU) population. The aim of this pilot study is to determine the feasibility of conducting a multicentre cluster randomised controlled trial (cRCT) in critically ill children comparing SDD with standard infection control. Methods and analysis: Paediatric Intensive Care and Infection Control is a parallel group pilot cRCT, with integrated mixed-methods study, comparing incorporation of SDD into infection control procedures to standard care. After a 1-week pretrial ecology surveillance period, recruitment to the cRCT will run for a period of 18 weeks, comprising: (1) baseline control period (2) pre, mid and post-trial ecology surveillance periods and (3) intervention period. Six PICUs (in England, UK) will begin with usual care in period 1, then will be randomised 1:1 by the trial statistician using computer-based randomisation, to either continue to deliver usual care or commence delivery of the intervention (SDD) in period 2. Outcomes measures include parent and healthcare professionals' views on trial feasibility, adherence to the SDD intervention, estimation of recruitment rate and understanding of potential patient-centred primary and secondary outcome measures for the definitive trial. The planned recruitment for the cRCT is 324 participants. Ethics and dissemination: The trial received favourable ethical opinion from West Midlands—Black Country Research Ethics Committee (reference: 20/WM/0061) and approval from the Health Research Authority (IRAS number: 239324). Informed consent is not required for SDD intervention or anonymised data collection but is sought for investigations as part of the study, any identifiable data collected and monitoring of medical records. Results will be disseminated via publications in peer-reviewed medical journals. Trial registration number: ISRCTN40310490 .